Onychostoma brevibarba, a new cyprinine fish (Pisces: Teleostei) from the middle Chang Jiang basin in Hunan Province, South China - Song, Xue-Ling; Cao, Liang; Zhang, E. (Zootaxa, 2018)
Onychostoma brevibarba, a new cyprinid species, is described from two tributaries flowing into the Xiang Jiang (= River) of the middle Chang Jiang basin in Hunan Province, South China. The new species is morphologically similar to two Chinese congeners, O. minnanense and O. barbatulum, but differs from them in the anteromedian extension of the postlabial groove. It further differs from O. minnanense in the maxillary-barbel length, shape and body coloration, and from O. barbatulum in the number of lateral-line perforated scales and the width of the mouth opening. The validity of the new species and its close relationship with these two species were affirmed by a molecular phylogenetic analysis based on the mitochondrial cyt b and CO1 genes.